Intentionality, Context, and the Semantics of Mawlā: A Schleiermacherian Reading of Ghadīr Khumm - Amin, Ainur Rofiq Al (Journal of Islamic Philosophy and Contemporary Thought, 2025)
The meaning of mawlā in the Ghadīr Khumm tradition remains one of the most contested issues in Islamic intellectual history, particularly within debates over religious authority and succession. While Shiʿi scholarship has predominantly interpreted the term as denoting authority and leadership, relatively little attention has been paid to the tradition through the lens of modern hermeneutical theory. This article re-examines the semantic and contextual dimensions of mawlā in Shiʿi narrations of Ghadīr Khumm by employing Friedrich Schleiermacher’s hermeneutics. Drawing on grammatical interpretation, psychological interpretation, and the hermeneutic circle, the study analyzes key Shiʿi textual sources in order to reconstruct the possible meaning of the Prophet’s declaration within its linguistic, historical, and discursive setting. The findings suggest that mawlā is most plausibly understood as a form of religiously grounded authority that extends beyond notions of friendship, loyalty, or patronage and is presented as continuous with the Prophet’s normative authority over the believing community. This interpretation demonstrates a higher degree of coherence with the narrative structure, rhetorical features, and historical circumstances of the Ghadīr event than alternative readings. By bringing classical Islamic materials into dialogue with modern hermeneutical theory, the article contributes to broader discussions on meaning, intentionality, and historical understanding in the study of religious texts, while also highlighting the epistemological limits inherent in reconstructing authorial intention from transmitted traditions.